Professional Engagement and Digital Competence in Teacher Performance; with the Moderating Variable of Supportive Work Environment: Case Study of MGMP Teachers in East Java - Eva Mufidah; Triesninda Pahlevi; Jaka Nugraha (PT Maju Malaqbi Makkarana, 2026)
Context and Relevance. Teacher performance is a key determinant of a teacher’s success in implementing to learning process in schools. Not all teachers can adapt to technological changes, including digital transformation. Although the school environment provides adequate support facilities, obstacles remain to the use of these learning technologies. This is no exception for MGMP teachers in East Java, who still face these obstacles. Objective. This research aims to improve teacher education programs by developing effective learning models to prepare future teachers professionally, including the application of the Digital Competence Framework for Educators. Hypothesis. To determine direct effect of professional engagement and digital competence on teachers performance. Furthermore, this study focuses whether a supportive work environment can strengthen the effect of professional engagement and digital competence on teacher performance. Methods and Materials. This research employs an explanatory research approach with purposive sampling, involving 100 MGMP teachers across East Java, and analyzes the data using Structural Equation Modeling (SEM). Results. This study indicates a professional engagement and digital competence have positive and significant effect on teachers performance. Meanwhile, a supportive work environment can strengthen the effect of professional engagement on teachers performance. However, a supportive work environment cannot enhance the effect of digital competence on teachers performance. Conclusions. In this study, the results indicated an increase in professional engagement and digital competence among MGMP teachers. These results become a focus for improving teacher professional development programs. Therefore, both educational institutions and local governments need to support the creation of a supportive work environment through managerial support. Digital infrastructure and teacher collaboration will affect the sustainability of academic progress in the modern era.